2023
DOI: 10.3389/fendo.2023.1027598
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic analysis of atypical parathyroid adenoma compared with parathyroid carcinoma and benign lesions in a Chinese cohort

Abstract: ContextThe malignant potential and molecular signature of atypical parathyroid adenoma (APA) remain elusive. Data from Asia are still lacking.Design and settingThis was a retrospective study on a large APA cohort in a single center from mainland China.MethodsA total of 320 patients with primary hyperparathyroidism (PHPT), containing 79 APA, 79 Parathyroid cancer (PC) and 162 benign lesions cases, were enrolled after surgery for collection of clinical data and genetic analysis.ResultsAPA patients showed earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 54 publications
0
8
0
7
Order By: Relevance
“…Conversely, in a recent paper, Chen et al. ( 19 ), reported that patients with AA presented clinical characteristics much less severe than PC. However, the same Authors showed that prevalence of nephrolithiasis/calcinosis and fragility fractures, as well as BMD values at lumbar and femoral sites were not significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Conversely, in a recent paper, Chen et al. ( 19 ), reported that patients with AA presented clinical characteristics much less severe than PC. However, the same Authors showed that prevalence of nephrolithiasis/calcinosis and fragility fractures, as well as BMD values at lumbar and femoral sites were not significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 91%
“…Concerning the biochemical presentation, our patients showed marked hypercalcemia associated with PTH levels higher than 10 times the upper normal range. Only few studies on small series compared biochemical features of PC and AA ( 11 14 , 19 ), reporting in the majority, though not all of them ( 11 , 19 ), similar PTH and calcium levels. Accordingly, we found no differences in the biochemical profile of the studied groups, indicating that PTH and calcium levels are not able to discriminate between PC and AA.…”
Section: Discussionmentioning
confidence: 99%
“…Bei der Suche nach einer oder mehreren vergrößerten Nebenschilddrüsen im Rahmen eines PHPT ist bei kritischer Hyperkalzämie häufig mit einer ektopen, auch intrathorakalen Lage beteiligter NSD zu rechnen [5]. Umgekehrt werden ektop gelegene NSD-Adenome und Nebenschilddrüsenkarzinome oft erst diagnostiziert, wenn sie zu einer kritischen Hyperkalzämie oder hyperkalzämischen Krise geführt haben [37,41].…”
Section: Diagnose Der Zugrunde Liegenden Erkrankungunclassified
“…intrathorakal mittels CT nachgewiesen [4,43]. NSD-Karzinome, die ebenfalls bei kritischer Hyperkalzämie häufiger diagnostiziert werden als bei gering erhöhten Serum-Kalzium-und Serum-Parathormonwerten [38,41,44], sind meist über 3 cm groß und weisen schon im Ultraschall intratumoröse Fibrosen und auch kleine Zysten auf [33].…”
Section: Diagnose Der Zugrunde Liegenden Erkrankungunclassified
See 1 more Smart Citation